Peningkatan Keterampilan Berbicara pada Siswa Sekolah Dasar di Merauke - Indriyani, Novi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
Speaking skills are one of the basic skills that must be possessed in mastering English. However, this speaking skill is challenging, considering English is a foreign language in Indonesia. Many factors ultimately become the cause of students' speaking skills needing to be improved. At the elementary school level, the researcher observed that students' speaking skills needed to be enhanced due to the lack of variety of activities provided and the lack of space for students to explore their speaking skills. This is what underlies the researchers to conduct activities to improve the speaking skills of elementary school-level students in Merauke. This activity involves teachers and students in grade 5 elementary school. The action begins with conducting interviews and preliminary observations of teachers and students, administering a pre-test to determine students' initial abilities, teaching to improve students' speaking skills, and conducting a post-test to measure the achievement of activity objectives. From these activities, the results showed that students experienced an increase in both self-confidence and speaking skills.